解:
a²+b²+c²=(a+b+c)²-2(ab+bc+ca)
ab+bc+ca=[(a+b+c)²-(a²+b²+c²)]/2=(2²-3)/2=1/2
a³+b³+c³=(a²+b²+c²)(a+b+c)-a²b-a²c-ab²-b²c-ac²-bc²
=3×2-(a²b+ab²)-(a²c+ac²)-(b²c+bc²)
=6-ab(a+b)-ac(a+c)-bc(b+c)
=6-ab(2-c)-ac(2-b)-bc(2-a)
=6-2ab+abc-2ac+abc-2bc+abc
=6-2(ab+bc+ca)+3abc
=6-1+3abc
=5+3abc=4
abc=-1/3
a⁴+b⁴+c⁴
=(a³+b³+c³)(a+b+c)-a³b-a³c-ab³-cb³-ac³-bc³
=4×2-(a³b+ab³)-(a³c+ac³)-(b³c+bc³)
=8-ab(a²+b²)-ac(a²+c²)-bc(b²+c²)
=8-ab(3-c²)-ac(3-b²)-bc(3-a²)
=8-3ab+abc²-3ac+ab²c-3bc+a²bc
=8-3(ab+bc+ca)+abc(a+b+c)
=8- 3/2 +(-1/3)×2
=8- 3/2 -2/3
=35/6